Microwave-Induced Synthesis of 2-Aminoimidazolines Under Neat Conditions - Genc, Murat; Servi, Sueleyman (Taylor & Francis Inc, 2009)
2-Aminoimidazolines were synthesized by the nucleophilic substitution reaction of 2-methylmercapto-4,5-dihydroimidazole hydroiodide with various amine compounds under neat conditions.
Keywords: 2-Aminoimidazolines; microwave irradiation; neat reaction